On the local and global asymptotic stability of the Degn‐Harrison reaction‐diffusion model. (29th October 2018) - Abbad, Abir; Bendoukha, Samir; Abdelmalek, Salem
Abstract : In this paper, we study the well‐known Degn‐Harrison reaction diffusion model. We are concerned with the local and global asymptotic stability of the system. Weaker conditions than those of previous studies are derived and validated using Matlab computer simulations.